Hydrogen-bonded, all-organic pebax/epigallocatechin gallate membranes for CO2 separation - Hwang, Junseok; Kang, Miso; Oh, Na Yeong; Kim, Jong Hak (Frontiers in Membrane Science and Technology, 2025)
This study systematically investigates the structural, thermal, mechanical, and gas separation properties of hydrogen-bond (H-bond) induced Pebax/epigallocatechin gallate (EGCG) membranes, emphasizing the role of EGCG as an H-bond inducer. Pebax® 1,657 membranes were fabricated via solution casting using a mixed solvent system of water and ethanol, with EGCG incorporated at varying concentrations (0–20 wt%) to assess its impact on membrane properties. The hydroxyl-rich structure of EGCG facilitates robust hydrogen-bonding interactions with the Pebax matrix, forming a transiently crosslinked structure. This strong interaction reduces the matrix’s free volume and alters its microstructure by decreasing the crystalline domain size of polyamide (PA) and enhancing the exposure of the amorphous poly (ethylene oxide) (PEO) chains in Pebax. At an optimal EGCG loading of 5 wt%, the membranes exhibited a CO2 permeability of 60.2 ± 1.1 Barrer and a CO2/N2 selectivity of 49.6 ± 0.8, representing a 33% increase in selectivity compared to pristine Pebax membranes. These performance enhancements are attributed to the reduction in fractional free volume (FFV) due to H-bond-induced structural modifications and the increased availability of amorphous PEO chains, which enhance CO2/N2 diffusivity selectivity and solubility selectivity, respectively. Moreover, mechanical testing demonstrated that the 5 wt% EGCG-incorporated membrane maintains its mechanical integrity, preserving the tensile strength of pristine Pebax while slightly improving elongation at break. Molecular dynamics (MD) simulations of FFV and solubilities corroborate the experimental observations, offering insights into the mechanisms underlying the improved gas separation performance. The results highlight EGCG as an effective H-bond inducer for tuning the properties of Pebax membranes, achieving an optimal balance between mechanical stability and gas separation efficiency at 5 wt% loading. This study provides a foundation for scaling up all-organic Pebax/EGCG membranes into high-performance membrane structures, presenting a promising approach for industrial CO2 separation and carbon capture applications.